Chelovek-prazdnik . Chelovek-prazdnik . A Festive Person . Человек-праздник - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program devoted to the film director Sergei Paradzhanov. Featured in the program: Akhmadulina, Bella Akhatovna (Poet) Contributors: Riazanov, El'dar (Anchor) Программа посвящена кинорежиссеру Сергею Параджанову. В программе участвуют: Ахмадулина, Белла Ахатовна (Поэтесса) Создатели: Рязанов, Эльдар (Ведущий/Ведущая)